Orlistat facilitates immunotherapy via AKT-FOXO3a-FOXM1-mediated PD-L1 suppression - Jie Li; Shiming Yang; Liting Wang; Xiaoyan Zhao; Changjiang Hu; Qingyun Tang; Lianhua Zhang; Shuo Zeng; Qiyu Bao; Weichao Hu; Lijiao He; Guiping Huang; et al. (Journal for ImmunoTherapy of Cancer)
Background The immunotherapy targeting cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) and programmed cell death ligand-1 (PD-L1) has achieved significant breakthroughs, but further improvements are still needed in cancer treatment.Methods We investigated orlistat, a drug approved by the Food and Drug Administration for the treatment of obesity and found that it can enhance the efficacy of CTLA-4 blockade immunotherapy. We conducted both in vivo and in vitro experiments to explore the mechanism by which orlistat increased antitumor immunity.Results Orlistat enhances the efficacy of anti-CTLA-4 immunotherapy by suppressing tumor cell PD-L1 protein expression and boosting the transcription of interferon-stimulated genes (ISGs) and MHC-I. Mechanistically, orlistat inhibits AKT activity and subsequent phosphorylation of forkhead box O3a (FOXO3a) at its threonine (T) 32, serine (S) 253, thereby downregulating Forkhead box M1 (FOXM1) expression, which ultimately suppresses PD-L1 transcription. Specifically, inhibition of FOXM1 leads to FOXO3a accumulation through impaired AKT activity. FOXM1 activates protein kinase B (AKT) via acting as a scaffold to facilitate 3-phosphoinositide-dependent protein kinase 1 (PDK1) and AKT and interaction. In addition, orlistat enhances phosphorylated signal transducer and activator of transcription 1 (p-STAT1) at tyrosine (Y) 701, resulting in upregulation of ISGs and MHC-I.Conclusions Orlistat plays a crucial role in modulating the immune response and supporting the combination with CTLA-4 blockade to promote antitumor immunotherapy.